3-D optical profilometry at micron scale with multi-frequency fringe projection using modified fibre optic Lloyd's mirror technique - GÖRK, GÜLŞEN (ELSEVIER SCI LTD, 2018)
A new fibre optic Lloyd's mirror method is developed for extracting 3-D height distribution of various objects at the micron scale with a resolution of 4 mu m. The fibre optic assembly is elegantly integrated to an optical microscope and a CCD camera. It is demonstrated that the proposed technique is quite suitable and practical to produce an interference pattern with an adjustable frequency. By increasing the distance between the fibre and the mirror with a micrometre stage in the Lloyd's mirror assembly, the separation between the two bright fringes is lowered down to the micron scale without using any additional elements as part of the optical projection unit. A fibre optic cable, whose polymer jacket is partially stripped, and a microfluidic channel are used as test objects to extract their surface topographies. Point by point sensitivity of the method is found to be around 8 mu m, changing a couple of microns depending on the fringe frequency and the measured height. A straightforward calibration procedure for the phase to height conversion is also introduced by making use of the vertical moving stage of the optical microscope. The phase analysis of the acquired image is carried out by One Dimensional Continuous Wavelet Transform for which the chosen wavelet is the Morlet wavelet and the carrier removal of the projected fringe patterns is achieved by reference subtraction. Furthermore, flexible multi -frequency property of the proposed method allows measuring discontinuous heights where there are phase ambiguities like 2 pi by lowering the fringe frequency and eliminating the phase ambiguity. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Lloyd's mirror; Fringe pattern analysis; Multi-frequency fringes; Optical profilometry; Wavelet transform; CONTINUOUS WAVELET TRANSFORM; SHAPE MEASUREMENT; MEASUREMENT SYSTEM; 3D PROFILOMETRY; REMOVAL; INTERFEROMETRY; DISPERSION; INSPECTION; PROFILE